2013
DOI: 10.1177/0883073813488664
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Topical Rapamycin Cream for the Treatment of Facial Angiofibromas in Tuberous Sclerosis Complex

Abstract: Facial angiofibromas are dermatological manifestations of tuberous sclerosis complex, a neurocutaneous disorder characterized by excess cell growth and proliferation. Oral rapamycin has been used to treat visceral tuberous sclerosis-related tumors; however, the side effect profile of this medicine precludes its routine use in patients lacking significant internal involvement. The authors formulated a novel rapamycin cream that is easy to compound and apply, does not cause local or systemic side effects, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 16 publications
1
31
0
2
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12][13] The articles were limited to those available in the English language and they were read, and any relevant articles referred to in the references were also included in the study. Of these, 11 were case series and one was a review article.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] The articles were limited to those available in the English language and they were read, and any relevant articles referred to in the references were also included in the study. Of these, 11 were case series and one was a review article.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Haemel et al [5] reported the first case study of a TSC patient treated with topical sirolimus for facial angiofibromas, which showed a clinically significant improvement. A subsequent group of studies [6][7][8][9][10], although most of them are assessed with relatively small numbers of patients, supported the successful role of topical sirolimus in the dermatological management of TSC patients. A recent publication of a phase 2 randomized clinical trial using topical sirolimus gel on facial angiofibromas in TSC showed consistent results in its efficacy and safety with the previous reports [11].…”
Section: Introductionmentioning
confidence: 99%
“…Any mutation in these genes lead to the dysregulation of this inhibitory process, leading to uncontrolled cell growth, proliferation and protein synthesis that results in multi-organ hamartomas. [2] This disorder has an incidence of 1/6000 births, and mostly affects the skin, kidneys, heart, brain and lungs. [1,3] The cutaneous manifestations of tuberous sclerosis complex include angiofibromas, forehead fibrous plaques, hypomelanotic macules or confetti-like lesions, periungual fibromas and shagreen patches.…”
Section: Discussionmentioning
confidence: 99%